2016
DOI: 10.1002/anie.201610782
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Self‐Sorting of [2+3] Salicylimine Cage Compounds

Abstract: An inherently chiral C -symmetric triaminotribenzotriquinacene was condensed in racemic and enantiomerically pure form with a bis(salicylaldehyde) to form [2+3] salicylimine cage compounds. Investigations on the chiral self-sorting revealed that while entropy favors narcissistic self-sorting in solution, selective social self-sorting can be achieved by exploiting the difference in solubility between the homochiral and heterochiral cages. Gas sorption measurements further showed that seemingly small structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
116
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(120 citation statements)
references
References 73 publications
1
116
0
3
Order By: Relevance
“…[1d,3] Metallopolymers,i nw hich monomer units come together through coordination to metal centers, [4] are capable of reorganizing both between and within polymer chains,t hanks to the reversibility of the coordinative interactions. [1e, 9] Recently,others [7a,10] and our group [11] have demonstrated that metallopolymers can be generated through subcomponent self-assembly,w herein amine and aldehyde subcomponents condense around metal ions to form dynamic covalent [12] C=Na nd coordinative N!Metal bonds simultaneously. [1e, 9] Recently,others [7a,10] and our group [11] have demonstrated that metallopolymers can be generated through subcomponent self-assembly,w herein amine and aldehyde subcomponents condense around metal ions to form dynamic covalent [12] C=Na nd coordinative N!Metal bonds simultaneously.…”
mentioning
confidence: 99%
“…[1d,3] Metallopolymers,i nw hich monomer units come together through coordination to metal centers, [4] are capable of reorganizing both between and within polymer chains,t hanks to the reversibility of the coordinative interactions. [1e, 9] Recently,others [7a,10] and our group [11] have demonstrated that metallopolymers can be generated through subcomponent self-assembly,w herein amine and aldehyde subcomponents condense around metal ions to form dynamic covalent [12] C=Na nd coordinative N!Metal bonds simultaneously. [1e, 9] Recently,others [7a,10] and our group [11] have demonstrated that metallopolymers can be generated through subcomponent self-assembly,w herein amine and aldehyde subcomponents condense around metal ions to form dynamic covalent [12] C=Na nd coordinative N!Metal bonds simultaneously.…”
mentioning
confidence: 99%
“…This strongly suggests that homochiral CC3 and CC3-RS/CC3-SR are more stable than other potential diastereomers such as, for example, a cage containing 1 S,S-CHDA and 5 R,R-CHDA vertices. Such chiral selfsorting has been reported recently in salicylimine cages; 21 in that case, both products could be retained in solution in certain solvents, thus allowing a detailed analysis of their relative energies. Such analysis is not possible in our system due to the very low solubility (<1 mg mL −1 ) of the CC3-R/CC3-S racemate.…”
mentioning
confidence: 55%
“…Der daraus erhaltene Festkçrper ist das erste Beispiel füre in einzelnes porçses organisches Material mit sowohl Mikro-als auch Mesoporen (intrinsisch und extrinsisch). [188] Während eine narzisstische Selbstsortierung normalerweise entropisch begünstigt ist, konnte in diesem Fall eine soziale Selbstsortierung wegen der geringeren Lçslichkeit der heterochiralen Strukturen erreicht werden. [113] Wahrscheinlich führen attraktive p-p-Wechselwirkungen zwischen den Untereinheiten zu einem wesentlichen Enthalpiegewinn, der den unvorteilhaften Entropiebeitrag der Catenierung überkompensiert.…”
Section: Mechanisch Verzahnte Systemeunclassified